A2_5 Can Babies Kill - Dickens, Elliott; Limbu, Sandip; Anderson, Dominic; Bhaad, Trisha (Physics Special Topics, 2022)
In this paper, we investigate the killing power of a babies scream and how the number of babies effects the killing power. We compare the decibels generated by the scream of individual and a group of babies, to the decibels needed to cause damage/kill a human, for a range of distances. We find that a huge number of babies are needed to maim/kill a human, with about 4 × 10^7 babies, at close proximity, are required to start to cause fatalities. 10^9 babies is found to cause fatalities, up to 10 m away.